2016
DOI: 10.1093/jxb/erw428
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of seed germination

Abstract: From a biomechanical perspective, the completion of seed (and fruit) germination depends on the balance of two opposing forces: the growth potential of the embryonic axis (radicle-hypocotyl growth zone) and the restraint of the seed-covering layers (endosperm, testa, and pericarp). The diverse seed tissues are composite materials which differ in their dynamic properties based on their distinct cell wall composition and water uptake capacities. The biomechanics of embryo cell growth during seed germination depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(200 citation statements)
references
References 171 publications
3
165
1
5
Order By: Relevance
“…It was shown that changes in latitude, longitude and altitude may result in variation in temperature, radiation, moisture and soil fertility, which influence seed yield and components [31,35]. Previous data indicate latitude exhibited a positive correlation with seed traits, whereas longitude and altitude showed a negative correlation with seed yield-related traits in several species [37,38]. The results of the current study differ with this observation, although some seed traits showed a positive correlation with latitude and a negative correlation with longitude and altitude (Table 4).…”
Section: Seed Yield and Components As Affected By Geographical Factorsmentioning
confidence: 99%
“…It was shown that changes in latitude, longitude and altitude may result in variation in temperature, radiation, moisture and soil fertility, which influence seed yield and components [31,35]. Previous data indicate latitude exhibited a positive correlation with seed traits, whereas longitude and altitude showed a negative correlation with seed yield-related traits in several species [37,38]. The results of the current study differ with this observation, although some seed traits showed a positive correlation with latitude and a negative correlation with longitude and altitude (Table 4).…”
Section: Seed Yield and Components As Affected By Geographical Factorsmentioning
confidence: 99%
“…This is likely to be important in dormancy regulation because the biomechanical constraints described during germination (Steinbrecher and Leubner-Metzger, 2017) are probably established by this competitive process during seed maturation. Much variation in seed morphology in angiosperms is determined by the ratio of embryo and endosperm in the mature seed.…”
Section: Tissue To Tissue Communicationmentioning
confidence: 99%
“…Rupture of the testa, or other outer covering structures, has been described to precede rupture of the endosperm in several species and is a crucial step in germination regulation (Puglia et al . ; Steinbrecher & Leubner‐Metzger ). In S. officinale nitrate was shown to stimulate the expression of genes involved in the regulation and sensitivity to germination hormones (Iglesias‐Fernández & Matilla ; Carrillo‐Barral et al .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike S. officinale, where testa rupture occurs below the micropylar region and proceeds transversally, in S. dentata it started within the micropylar region and expanded longitudinally (Carrillo-Barral et al 2013;Toorop 2015), similar to Arabidopsis thaliana (Liu et al 2005). Rupture of the testa, or other outer covering structures, has been described to precede rupture of the endosperm in several species and is a crucial step in germination regulation (Puglia et al 2015;Steinbrecher & Leubner-Metzger 2017). In S. officinale nitrate was shown to stimulate the expression of genes involved in the regulation and sensitivity to germination hormones (Iglesias-Fern andez & Matilla 2010;Carrillo-Barral et al 2014;Matilla et al 2015).…”
Section: Discussionmentioning
confidence: 99%